Perkembangan Kristologi Abad Pertama - Eny Emelia Hewuni; Mitra Fitria; Reyhan Revando; Sarmauli Sarmauli (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study aims to determine the development of Christology in the first century. This study uses a qualitative approach with a library research type. Data analysis techniques use content analysis and historical-theological analysis. The results of the study found that the understanding of the development of Christology from the first to the fifth century was a long journey in which the church attempted to formulate a precise understanding of the person of Jesus Christ. Starting from the testimony of the apostles in the New Testament, Christological thought developed through challenges from Gnosticism, Arianism, Nestorianism, and Monophysitism. Through ecumenical councils such as Nicaea (325 AD), Constantinople (381 AD), Ephesus (431 AD), and Chalcedon (451 AD), the church established the doctrine that Jesus Christ is true God and true man, with two natures united in one person without mixing, without changing, without dividing, and without separating. Figures such as Ignatius, Irenaeus, Athanasius, Cyrillus, and Leo the Great played an important role in this formulation. This understanding of historical Christology remains a solid foundation for Christian faith to this day